Is Organic or Conventional Farming Better for Biodiversity? - Rainer Maurer (Wirtschaftsdienst)
Abstract This article compares the impact of organic and conventional farming on biodiversity. Two opposing effects are taken into account: the higher biodiversity of organic farming and the lower land use of conventional farming. An evaluation of both effects on the basis of empirical data shows that the higher biodiversity on organically cultivated areas is not sufficient to compensate for the higher land use of organic farming. For example, if a complete transition from conventional to organic farming takes place, average yields will decrease by at least 50 %, while the total biodiversity would increase by only 108 %. In contrast, if conventional farming yields were reduced by the same amount, 50 % of agricultural land could be renaturated. This would lead to an increase in total biodiversity of 317 %.